Plasmodium falciparum malaria vaccines: current status, pitfalls and future directions. (September 2012) - Salvador, Aiala; Hernández, Rosa M; Pedraz, José Luis; Igartua, Manoli
Currently, a vaccine against malaria has not yet been licensed. Different approaches have been explored with different immune responses, but neither has fulfilled the criteria for being approved. The most advanced candidate, RTS, S, is undergoing Phase III studies and comprises virus-like particles, liposomes and immunostimulatory molecules. Other strategies are based on the use of polymeric particles, viral vectors or virosomes. Here, the authors have summarized the clinical advances that have been made in the field of Plasmodium falciparum to date, since it is the main causal agent of severe malaria. The best strategies to further develop a vaccine against malaria have also been discussed. In fact, an appropriate formulation should be immunogenic, safe and well tolerated, and as far as possible, avoid the use of needles and require a low number of immunizations. Moreover, issues such as storage, costs and so on, have to be taken into account.